Let the current age of the boy be \( b \) and the current age of the father be \( f \). According to the problem, we have the following relationships:
-
The boy is 24 years younger than his father: \[ b = f - 24 \]
-
After two years, the sum of their ages will be 40: \[ (b + 2) + (f + 2) = 40 \]
We can simplify the second equation: \[ b + f + 4 = 40 \] Subtracting 4 from both sides gives: \[ b + f = 36 \]
Now we have two equations:
- \( b = f - 24 \)
- \( b + f = 36 \)
We can substitute the first equation into the second: \[ (f - 24) + f = 36 \]
Combining like terms, we get: \[ 2f - 24 = 36 \]
Adding 24 to both sides: \[ 2f = 60 \]
Dividing by 2: \[ f = 30 \]
Now, using the first equation to find the boy's age \( b \): \[ b = f - 24 = 30 - 24 = 6 \]
Finally, the father's current age is: \[ \boxed{30} \]